“ACTIVIDAD ANTIFÚNGICA “IN VITRO” DE ACEITE ESENCIAL Y EXTRACTO ALCOHÓLICO DE Mentha piperita “HIERBA BUENA” SOBRE Candida albicans CEPA ATCC 10231”. - Flores Colcha, Karina Fernanda (2017)
To compare the antifungal activity "In vitro", of essential oil and alcoholic extract of Mentha piperita (Good grass), by means of a microbiological study on strains of Candida albicans ATCC 10231. The methodology was carried out an experimental, comparative, in vitro, of essential oil and alcoholic extract of Mentha piperita (Good grass) at different concentrations, applied on strains of Candida albicans ATCC 10231 grown in Petri dishes, making a sowing of essential oil and alcoholic extract of Mentha piperita through the sweeping technique with the help of a swab, placing the Petri dishes in an incubator for 48 hours at 37º C for the subsequent reading of the inhibition halo. The results are the scale of essential oils according to Duraffourd it was identified that the Candida albicans against higher concentrations of essential oil of Mentha piperita presented a null activity. As for the alcoholic extract of Mentha piperita, the average inhibition halo was less than 3 mm. The comparison of the antifungal activity derived from the alcoholic extract and the essential oil of Mentha piperita, on strains of Candida albicans, showed that the antifungal effect of the oil is better than that obtained with the alcoholic extract, this depending on the diameter of the halo reported inhibition